2021
DOI: 10.3390/antibiotics10121440
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Heat Treatment of Food on Antimicrobial Resistance Genes and Their Potential Uptake by Other Bacteria—A Critical Review

Abstract: The dissemination of antibiotic resistance genes (ARGs) is a global health concern. This study identifies and critically reviews the published evidence on whether cooking (heating) food to eliminate bacterial contamination induces sufficient damage to the functionality of ARGs. Overall, the review found that there is evidence in the literature that Antimicrobial Resistant (AMR) bacteria are no more heat resistant than non-AMR bacteria. Consequently, recommended heat treatments sufficient to kill non-AMR bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 88 publications
(150 reference statements)
1
9
0
Order By: Relevance
“…This response was similar to that of fresh Bacillus culture (8 log CFU g À1 ), as previously reported by Khullar et al (2022). Although several reports insisted that heat treatment could induce antibiotic and antimicrobial resistance in cells (James et al, 2021;Ko & Bai, 2022), the results from this study demonstrated that the drying process did not deleteriously affect AMR and/or ARGs properties of Bacillus 63-11 strain.…”
Section: Effect Of Drying On General Probiotic Properties Of Bacillus...supporting
confidence: 89%
“…This response was similar to that of fresh Bacillus culture (8 log CFU g À1 ), as previously reported by Khullar et al (2022). Although several reports insisted that heat treatment could induce antibiotic and antimicrobial resistance in cells (James et al, 2021;Ko & Bai, 2022), the results from this study demonstrated that the drying process did not deleteriously affect AMR and/or ARGs properties of Bacillus 63-11 strain.…”
Section: Effect Of Drying On General Probiotic Properties Of Bacillus...supporting
confidence: 89%
“…Collectively, the higher use of antimicrobials is a confounding factor contributing towards AMR [ 6 ]. Furthermore, increasing AMR in zoonotic pathogens that may not necessarily cause diseases in animals, such as Salmonella and Campylobacter [ 7 ], and the dissemination of such resistant bacteria and/or AMR genes to humans [ 8 ], are even more concerning. If no actions are taken, the global sales and use of antimicrobials are expected to rise until 2030 on all continents, primarily in developing countries, as commercial livestock growth is higher in these countries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such genetic linkage between metaland antibiotic-resistance traits has been reported on plasmids in Enterobacteriaceae and in other bacteria isolated from other animal feces, soil, or sewage (47)(48)(49)(50). It has been shown that metals used in animal feed accumulate and persist in food animals, and may impact the development of AMR in primary animal and food production environments (51). Many studies indicate that the spread of AMR introduced through the application of manure to agricultural fields leads to its further spread within the food chain, and may pose a risk to human health (17,(52)(53)(54).…”
Section: Discussionmentioning
confidence: 78%